SUPPLY CHAIN USAHA KECIL MENENGAH (STUDI KASUS INDUSTRI BATIK TULIS LASEM KABUPATEN REMBANG) - Muhammad Tahwin; Dian Ayu Liana Dewi; A. Aviv Mahmudi (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Small and medium size enterprises are the   enterprise sectors that have significant contributions for economic development. Generally, small enterprises face many problems in their developments. One of the problem is supply chain management. Supply chain management concerns with the management in getting basic commodity from the suppliers through the factories and storeroomsuntil the products reach   the consumers. This problem is also faced by Batik Lasem Industry. The problems faced are the difficulty in getting basic commodity, low abilities in marketing the products and make marketable products from input to output (supply chain problem).This researchaim is to find the efficient supply chain model for Batik Lasem Industry. The data analysis used is qualitative approach. The analysis is carried out by supply chain component (supplier, factory, distributor and consumers) which is categorized into supply chain cycles. From the result of focus group discussion concluded that supply chain model applied by Batik Tulis Lasem Industry ismodel of basic commodity supply and product distribution without agents, model of basic commodity supply with agents and product distribution without agents, model of basic commodity supply without agents and product distribution with agents, and basic commodity supply anddistribution model with agents. The Implication of this research result is the importance of supplychain model testing so developing of Batik Tulis Lasem Industry can carried out with effective andefficient model.Key words: supply chain, agent, Batik Lasem.